Case Report: Quantitative multimodal imaging for surgical planning in isolated pulmonary artery sling - Ye, Tianhe; Liu, Cong (Frontiers in Pediatrics, 2026)
BackgroundPulmonary artery sling (PAS) is a rare congenital vascular anomaly in which the left pulmonary artery (LPA) originates from the right pulmonary artery (RPA), forming a ring around the tracheobronchial tree. Due to non-specific respiratory symptoms, it is frequently misdiagnosed, leading to significant delays in diagnosis. This report emphasizes the crucial role of quantitative multimodal imaging in establishing a definitive diagnosis, stratifying risk, and guiding optimal surgical planning.Case presentationA 4-year-and-7-month-old boy presented with a 4-year history of recurrent cough and wheezing that was refractory to standard medical therapy. Echocardiography revealed a dilated main pulmonary artery (MPA) measuring 1.9 cm (Z-score +3.2) and an anomalous origin of the LPA from the RPA, with an elevated peak flow velocity of 1.75 m/s. Contrast-enhanced computed tomography angiography (CTA) subsequently confirmed a Type I PAS, enabling precise quantification of a severe focal stenosis of the LPA (minimal diameter 2.8 mm) and demonstrating the absence of significant intrinsic tracheobronchial stenosis. Based on these findings, the patient underwent successful reimplantation of the LPA onto the MPA with an autologous pericardial patch. The postoperative course was uneventful, with complete resolution of respiratory symptoms, and follow-up imaging confirmed a patent anastomosis with successful hemodynamic outcomes.ConclusionsThis case of isolated PAS underscores the indispensable role of a multimodal imaging strategy. While echocardiography can provide initial clues, quantitative CTA is paramount for definitive anatomical classification, precise stenosis quantification, and comprehensive preoperative planning. Early consideration of PAS in children presenting with refractory respiratory symptoms, coupled with advanced imaging, can prevent misdiagnosis and optimize outcomes.